2004
DOI: 10.1007/s11141-005-0011-z
|View full text |Cite
|
Sign up to set email alerts
|

Polarization dynamics of longitudinally monomode bipolarized microchip solid-state lasers

Abstract: UDC 621.373This paper is devoted to the polarization dynamics of a longitudinally monomode bipolarized Nd:YAG laser: the low-frequency polarization dynamics of a microchip laser is studied experimentally and theoretically. The intensities and the relaxation oscillation spectrum of orthogonally polarized modes versus the direction of pump polarization is observed. A phase-sensitive model of a longitudinally monomode bipolarized solid-state laser with linear polarized diode laser pump is developed to account for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 24 publications
2
13
0
Order By: Relevance
“…1(c,d), the pump polarization controlled the laser output power in each polarization direction, giving excellent agreement with the rateequation model. In addition, the output power variations with pump laser polarization angles are consistent with those observed in Refs [15][16][17]24] but experimental tests of the power dependence on the crystal angle are not practical due to the small power variation predicted. Fig.…”
Section: Anisotropic Rate Equationssupporting
confidence: 84%
See 2 more Smart Citations
“…1(c,d), the pump polarization controlled the laser output power in each polarization direction, giving excellent agreement with the rateequation model. In addition, the output power variations with pump laser polarization angles are consistent with those observed in Refs [15][16][17]24] but experimental tests of the power dependence on the crystal angle are not practical due to the small power variation predicted. Fig.…”
Section: Anisotropic Rate Equationssupporting
confidence: 84%
“…Refs [15][16][17] discuss the impact of pump polarization on the ROs but without considering the crystal angle and pump-polarization. We previously studied both pump-polarization and crystal-orientation effects in a (100)-cut Nd:YAG dual-polarization laser [7].…”
Section: Relaxation Oscillation Frequenciesmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the instability is caused by the mode interaction, a new comprehensive model of a multimode laser with intracavity frequency doubling should more accurately take into account such important properties of the laser as the spatial [8,10,11] and angular [9,13,19] inhomogeneity of the gain.…”
Section: Discussionmentioning
confidence: 99%
“…The phase anisotropy may be due to the small residual birefringence in the crystal of the active element, while the amplitude anisotropy of the active medium - by the gain anisotropy induced by linearly polarised pump radiation [7]. It is shown that the change in orientation of the NE axes (rotation in a plane perpendicular to the cavity axis through 45° relative to the direction of mode polarisations of a bipolarisation laser) without additional phase plates can result in optimal conditions for steady-state generation.…”
mentioning
confidence: 99%